Quality Of Preparation Of Lectures On Technical Subjects - Atajanova Malika Zafar kizi (Global Scientific Publishing, 2025)
The article examines issues related to improving the quality of preparation of lectures on technical disciplines in higher educational institutions. The importance of the lecture as a form of organizing the educational process, especially in engineering education, is emphasized. The main factors influencing the effectiveness of lecture teaching are analyzed, including didactic development of content, the use of modern information and communication technologies, the level of pedagogical competence of the teacher and the degree of integration of lecture material with practical and laboratory classes. Recommendations are presented for optimizing the preparation of lectures in order to improve the level of assimilation of educational material by students of technical specialties.
Keywords: lecture; technical disciplines; quality of education